The Effectiveness Between Tamsulosin and Solifenacin Combined with Tamsulosin on Treatment of Ureteral Stent-Related Symptoms - Syarif Bakri; Syakri Syahrir; Firdaus Kasim; Berry Erida Hasbi; Muhammad Asykar Palinrungi; Khoirul Kholis (Faculty of Medicine, Hasanuddin University., 2021)
Introduction: The clinical usage of the ureteral stent caused several stent-related symptoms (SRSs), including lower urinary tract symptoms, pain, general health, work performance, sexual matter and additional problems. This study aims to evaluate the effectiveness between tamsulosin and solifenacin combined with tamsulosin for SRSs.Methods: This double blind randomized controlled trial used 50 patients. Between September 2020 and February 2021, patients underwent double-J stenting after retrograde ureteroscopy were analyzed. All patients would be randomized in a 1:1 ratio in a 1:1 ratio to receive either tamsulosin 0,4 mg (Group A: 25 participants) or tamsulosin 0,4 mg & solifenacin 5 mg combination (group B: 25 participants).We used the Ureteral Symptoms Score Questionnaire (USSQ) as an outcome measure at 1s, 2nd, 3rd and 4th weeks after stent insertion. Results: Group A was found more in women, while in group B was more in men. The highest age in group A and group B was 50-60 years old (36% and 64%). The location of stenting in group A was found more in left (60%), while the group B in the right (52%). Both groups had more patients who were normal nutritional status (60%). There was an improvement in pain and work performance after treatment in both groups, meanwhile group B showed better improvement than group A at all weeks. in addition, there was an improvement in urinary symptoms and sexual matter in group B better than in group A at 2nd to 4th week. Furthermore, group B showed better improvement in general health and additional problem only at 4th week. Conclusions: Combination therapy with tamsulosin and solifenacin improved USSQ score more than the monotherapy group. This implied that combination therapy is optimal for improving SRSs.